Avaliação e promoção de locais de interesse geomorfológico (LIGeom) do Cânion do rio Poti, Ceará/Piauí, Brasil: subsídios ao Geoturismo - Silva, Helena Vanessa Maria da (2024)
The Poti River Canyon is located in the northeast of Brazil, on the border between the states of Ceará (CE) and Piauí (PI) and corresponds to an incised U-shaped valley that splits the sandstones of the Serra Grande Formation, oriented in an E-W direction. It is a structural valley controlled by NE-SW fracture systems (“Transbrasiliano” structural lineaments). In the area, there are several waterfalls, natural pools, lookouts, caves and karst morphology in sandstone.In addition to these geomorphological attractions, the Canyon of the Poti River hosts paleontological manifestations such as ichnofossiliferous outcrops and has cultural resources associated with geomorphological heritage such as a wealth of archaeological sites (engravings and cave paintings) in association with historical and religious aspects. In view of this, this study aims to promote the potential of the Sites of Geomorphological Interest (LIGeom) of the Poti River Canyon region based on geoconservationist strategies using interpretive and informative tools, in order to encourage geotourism in the area. To this end, the methodology was divided into: i) collection of bibliographical references, documents and technical reports; ii) office work to create cartographic material; iii) recognition inventory based on Sharples (2002); iv) field work; v) inventory and vi) proposing strategies for the promotion the LIGeom evaluated. The methodology used in the inventory stage was based on Araújo (2021) e Araújo et al., (2024), while the proposal for the Website on Arruda, Mariano and Guimarães (2024). In the inventory stage, twelve Sites of Geomorphological Interest with potential for geotourism were identified and qualitatively assessed, based on geomorphological characterization and qualification. Besides geomorphological particularities and potentialities, the Sites of Geomorphological Interest evaluated reveal distinct characteristics that make it possible to understand the Geology (Sedimentology and Stratigraphy), Paleontology and Archeology of the area. One concludes that there is a need to think about the existing tourist trade in the territory in order to operate geotourism; despite the existence of tourist guides and drivers and tourist agencies, the Poti River Canyon region still lacks infrastructure in terms of the services offered, such as hotels, restaurants, access and accessibility to local potential, and also to think about how to qualify leisure tourism, such as geotourism, for example. One expects that the work of the different spheres of government, especially at municipal and state levels, together with private initiatives and, in particular, local residents, will lead to measures that guarantee the conservation and promotion of this valuable geodiversity.